Suspicion : vaccines, hesitancy, and the affective politics of protection in Barbados - Charles, Nicole, 1989- (Duke University Press, 2021)
"Nicole Charles frames the refusal of Afro-Barbadians to immunize their daughters with the HPV vaccine as suspicion, showing that this suspicion is based in concrete histories of government mistrust and coercive medical practices on colonized peoples."--